Information Awareness When Applying For Postgraduate Studies At The University Of Baghdad And Its Relation To The Ethics Of Their Scientific Research - Naji kadom, Israa (Opción, 2019)
The current research aims to know the information awareness among grad- uate students at the University of Baghdad and its relationship with the eth- ics of scientific research have, the researcher adopted a descriptive research methodology to correspond with the problem of research and its goal, has been the number of research tools, which was the first tool measure of infor- mation awareness of (24) paragraph distributed number Paragraphs of the scale equally on the six areas, (four paragraphs for each field) and in order, the four-step scale was selected on the basis of the Descartes quartet scale and scores (1,2,3,4) for each positive paragraph and was given a score (4,3,2,1) for paragraphs The negative four paragraphs were represented by the following paragraphs (22,11,10,6). For a second was the measure of ethics of scientific research consists of (30) paragraph three fields (cognitive, skill, sentimental) distributed the number of paragraphs of the scale equally on the three fields, (ten paragraphs for each field), the scale was chosen quadratic scale according to the scale of Descartes and gave four grades for each Paragraph (1,2,3,4) for each positive paragraph was given a score (4,3,2,1) for the negative para- graphs and the five paragraphs were represented by paragraphs (29,22,9,4,2), the research sample consisted of (42) Postgraduate students (11) doctoral stu- dents and (31) master students, the results showed that the graduate students have an awareness of information by 64.3% and more than doctoral students Balu There is no difference between the two phases in the ethics of scientific research.